Effectiveness of Small Holder Tea Cultivation as a Sustainable Livelihood: Case Study of Palinda-Nuwara Divisional Secretariat (DS) Division in the Kalutara District - Bandula, H. D. A. C. (My University, 2008)
Smallholder tea cultivation is the main commercial agricultural crop in low and mid country wet-zone in Sri Lanka. The purpose of this study is to investigate its capacity and performance as a resilient livelihood approach. The study has two main purposes (1) to investigate its relative economic contribution compared to other sources and (2) to examine the financial performance of it in business perspective in rural economy. The study was conducted in Palindanuwara Divisional Secretariat Area (DS) in Kalutara district. The empirical part of the study was conducted in three Grama Niladari Divisions in the division. Data for this study were mainly collected through pre-tested structured questionnaire based household survey by covering hundred tea small holder households. Stratified random sampling techniques are used to determine the sample frame. The results of the study reveal that tea is the main income source of tea small holders with highest significance. However it considerably varies from higher to lower elevations in the geography of the area. The cost incurs for tea is represented heavy portion of their total expenditure volume. It was found that land and labour are the key resources with number of constraints in terms of availability and ownership. Male and female family labour covered the significant portion of the labour need but varies in different agricultural practices. It was proved that the high level of net profit from tea small holdings mainly determined by the scale of cultivation. However drought has significant impact on the yield levels. The study further found that the very poor application of risk reduction agronomic practices by tea small holders. However the level of their satisfaction and expectations on future of the industry is at extremely higher standard according to their perceptions. ...